Morphological study of SiO₂ biocomposite / Iskandar Zulkarnain Mohd Zaidi - Mohd Zaidi, Iskandar Zulkarnain (2019)
In recent years, the world have shown developing enthusiasm for natural fibers as strengthening material in composites fundamentally because of ecological concerns and consciousness of constraining non-renewable resources to deliver petrochemical based engineered polymers. Natural fiber that is used to reinforce composite has the presence of silica bodies. Though the general effect of silica bodies in the plant contribute to the growth of the plants is known, the real effect of its function towards the strength of composite remains unclear. The objectives of this study are; (1) to study the morphology of SiO₂ biocomposite; and (2) to study the SiO₂ effect towards the biocomposite strength. The OPMF grafting LLDPE (OPMF-g-LLDPE) was produced via twin-screw extruder and hot press moulding at varying fibres content. The biocomposite of LLDPEg-MA/SiO₂ was prepared in three different weight percent (wt%) which are (93,2,4,1), (91,4,4,1) and (89,6,4,1) that represent weight percent of LLDPE, SiO₂, peroxide and maleic anhydride. This study is attempting to imitate or mimic the composition of SiO₂ in oil palm mesocarp fiber (OPMF). The results are obtained by performing scanning electron microscopy (SEM) analysis with variation of different SiO₂ insertion based on the effect of cutting techniques and the surface of the sample being rubbed by sand paper. The SiO₂ insertion used is 5wt%, 10wt% and 15wt%. The results showed that there are different morphological features for different cutting techniques, which is cutting by using liquid nitrogen and due to tensile stress. The results also showed that the SiO₂ granules have irregular shapes as they have sides and angles of any length and size. There are also clearer signs of agglomeration in the composite with lower content of SiO₂. The study concluded that as the fiber weight increases, the strength of the resulting composite is also increases.